2000
DOI: 10.1046/j.1469-7580.2000.19630415.x
|View full text |Cite
|
Sign up to set email alerts
|

Normal growth and development of the lips: a 3‐dimensional study from 6 years to adulthood using a geometric model

Abstract: A 3-dimensional computerised system with landmark representation of the soft-tissue facial surface allows noninvasive and fast quantitative study of facial growth. The aims of the present investigation were (1) to provide reference data for selected dimensions of lips (linear distances and ratios, vermilion area, volume) ; (2) to quantify the relevant growth changes ; and (3) to evaluate sex differences in growth patterns. The 3-dimensional coordinates of 6 soft-tissue landmarks on the lips were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(43 citation statements)
references
References 26 publications
(45 reference statements)
3
39
0
Order By: Relevance
“…In the 12-to 13-year-old group, most of the girls experienced their adolescent growth spurt with a particularly evident growth in vertical facial dimensions that surpassed male growth in the same direction (Ursi et al, 1993;Prahl-Andersen et al, 1995). Whereas females practically ended their softtissue craniofacial growth in this age group (Nanda et al, 1990;Ursi et al, 1993;Bishara et al, 1997;Ferrario et al, 1998bFerrario et al, , 1999cFerrario et al, , 2000, males continued their growth (and aging) even after 30 years of age (Nanda et al, 1990;Foley and Mamandras, 1992;Bishara et al, 1997;Gualdi-Russo, 1998;Ferrario et al, 1999aFerrario et al, ,c, 2000.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In the 12-to 13-year-old group, most of the girls experienced their adolescent growth spurt with a particularly evident growth in vertical facial dimensions that surpassed male growth in the same direction (Ursi et al, 1993;Prahl-Andersen et al, 1995). Whereas females practically ended their softtissue craniofacial growth in this age group (Nanda et al, 1990;Ursi et al, 1993;Bishara et al, 1997;Ferrario et al, 1998bFerrario et al, , 1999cFerrario et al, , 2000, males continued their growth (and aging) even after 30 years of age (Nanda et al, 1990;Foley and Mamandras, 1992;Bishara et al, 1997;Gualdi-Russo, 1998;Ferrario et al, 1999aFerrario et al, ,c, 2000.…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of the largest sexual differences in global facial morphology showed that males had a larger forehead, more inferior and posterior gonia, more inferior and prominent nose and lips, and larger mouth than females of corresponding age (Genecov et al, 1990;Ferrario et al, 2000). The largest shape discrepancies were observed in the facial lower third, which was larger, more anterior and inferior in males than in females, in the zygomatic region, with more anterior cheeks in females, and in the forehead, with a more anterior trichion landmark in females (Ferrario et al, 1999c).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The subject's face was well illuminated. Before taking photograph of each subject, one physical measurement was taken by a slide caliper between two angles of the mouth (chilion to chilion) 9 . By using this individual physical value, each photograph was converted into actual size.…”
Section: Methodsmentioning
confidence: 99%
“…12 Lips development in boys were larger than in girls, and attainment of adult dimensions was faster in the upper than in the lower. 13 The lips and the other soft tissues of the face sag downward with aging, and become progressively thinner with less vermillion display. Environmental influences during growth and development of the face, jaws, and teeth consist largely of pressures related to the physiologic activity.…”
mentioning
confidence: 99%